Pancreatic carcinoma masked as fever of unknown origin: A case report and comprehensive review of literature. Issue 35 (August 2016) - Shi, Ning; Xing, Cheng; Chang, Xiaoyan; Dai, Menghua; Zhao, Yupei
Abstract: Background: Pancreatic carcinoma is a highly lethal malignancy. Common presenting features of pancreatic cancer include anorexia, asthenia, weight loss, pain, and obstructive jaundice. Nevertheless, fever as a symptom, or even primary manifestation of pancreatic cancer is rather rare. Methods: Here, we report a 63-year-old male patient presenting with daily fevers, night sweats, and fatigue of 2-month duration. Laboratory findings showed elevated white blood cell count (WBC), erythrocyte sedimentation rate (ESR), and serum C-reactive protein (CRP). A computed tomography scan demonstrated a tumor between the duodenum and pancreatic head. Chest radiograph was normal. Results: The patient underwent an uneventful tumor resection. Histological examination of a surgical specimen demonstrated an undifferentiated adenocarcinoma originated from pancreatic head. The tumor was compatible with TNM stage IIA (T3N0M0). Complete resolution of the fever was achieved on post-operative day 4 and no recurrence of the tumor or neoplastic fever happen during the 39-month follow-up. Conclusion: Pancreatic adenocarcinoma could manifest as neoplastic fever at the time of diagnosis. If the tumor is resectable, surgical resection is a safe and curative form of therapy not only for the fever but also for the original carcinoma.